Effect of Application of Discovery Learning Model Assisted by Mind Map Against Competence Learning Learners in Junior High School 28 Padang - Siska Febritama; Rahmawati D. Rahmawati D.; Siska Alicia Farma; Helendra Helendra (Universitas Negeri Padang, 2020)
The results of the achievement of science learning competencies at junior high School 28 Padang are still low because the learning process is still teacher-centered, and the teacher still uses the lecture method. Students tend to be passive in the learning process. One way that is used to motivate and activate students in a pleasant atmosphere is to apply mind map assisted discovery learning models.This type of research is quasi-experimental research with the design of randomized control-group posttest only design. The population of this study was all VII grade students of SMP 28 Padang who were enrolled in the 2018/2019 Academic Year. Sampling is done by purposive sampling technique. so Class VII2 was chosen as the experimental class and class VII1 as the control class. The research data includes learning outcomes from three domains, namely cognitive, affective and psychomotor. The research instruments were in the form of learning outcomes tests, affective domain observation formats and psychomotor assessment sheets. The data obtained were analyzed using the t-test. T test is obtained t count>table which is 4.66> 1.66 in knowledge competency, 2.76> 1.66 in attitude competency, and 3.62> 1.66, in skill competency. Thus it can be concluded that by implementing mind map assisted discovery learning models, it has a positive effect on students' learning competencies in junior high school 28 Padang